Efikasi dan Keamanan Penggunaan Terapi Kombinasi Broadly Neutralizing Monoclonal Antibodies (bNAbs) untuk Menekan Kadar Viremia pada Pasien HIV-1: Sebuah Tinjauan Literatur - Maulana, Syafiq (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Human Immunodeficiency Virus type 1 (HIV-1) remains a global health challenge with persistently high infection and mortality rates. Current antiretroviral therapy has not been able to completely eliminate the virus, highlighting the need for long-term alternative treatment strategies. The combination of broadly neutralizing antibodies (bNAbs) has emerged as a promising approach to suppress viremia and improve long-term control of HIV-1. Methods: This literature review was conducted by searching scientific articles in the PubMed and ScienceDirect databases using specific keywords related to bNAbs and HIV-1. Article selection was based on predefined inclusion and exclusion criteria, resulting in seven clinical trial articles for further analysis. Discussion: Current evidence shows that combination bNAbs offer improved efficacy and safety in addressing the genetic diversity of HIV-1 and preventing the emergence of resistance. The use of double, triple, and quadruple bNAb combinations has been shown to broaden viral neutralization and optimize long-term plasma viremia control. Favorable safety profiles in clinical trials support the potential of bNAbs as a promising long-term therapeutic candidate. However, most included studies had limited sample sizes and did not assess the long-term effects of the therapy. Conclusion: Combination bNAb therapy has the potential to become an effective and sustainable strategy in the management of HIV-1. Larger-scale studies are needed to strengthen clinical evidence and optimize its implementation.   Keywords: HIV-1, bNAbs combinations, virology, therapy